Early Experiences with Indigenous Medicated Spacers in the Management of Infected Hip Prosthesis. - Chand, Pankaj; Magar, Suchil Rana; Thapa, Bishnu Babu; KC, Bachhu Ram; Joshi, Amit; Kayastha, Nirab (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Joint replacement surgery, has become one of the most frequent prosthetic surgeries over the past decades due to its success in restoring function to disabled arthritic individual. A two-stage revision arthroplasty is a well-accepted method for the treatment of a deep infection of a hip with a joint implant. In the present study, the results of three infected hips with the interim use of an indigenous cemented prosthesis along with gentamycin impregnated cement beads were assessed with a two stage revision. Methods: Three consecutive patients who were managed with a two-stage revision hip arthroplasty for the treatment of a previous infection, with retained implants, were followed clinically and radiographically for an average of 15 months. Following removal of implants and debridement (first stage), an indigenous medicated prosthesis along with antibiotic coated cement beads were implanted, for an interim phase of six - eight weeks aft er which a new prosthesis was placed ( second stage ).In this period antibiotics ( both intravenous and oral) were administered to the patients. Results: In a mean follow up period of 15 months, there is no evidence of recurrent infection in all three patients, as of now. The use of antibiotic coated cement prosthesis along with gentamycin mixed cement beads was associated with a satisfactory hip score, and better walking capacity in the interim period, a lower transfusion requirement at the time of reimplantation, and no postoperative dislocation. Conclusions: Locally prepared medicated spacer and gentamycin coated beads help in eradicating hip infection, besides being more cost effective. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/32-36 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7765